Memory, language, and bilingualism : theoretical and applied approaches - Altarriba, Jeanette, 1964-; Isurin, Ludmila (Cambridge University Press, 2012)
"The relationship between memory and language and the topic of bilingualism are important areas of research in both psychology and linguistics and are grounded in cognitive and linguistic paradigms, theories and experimentation. This volume provides an integrated theoretical/real-world approach to second language learning, use and processing from a cognitive perspective. A strong international and interdisciplinary team of contributors present the results of various explorations into bilingual language processing, from recent advances in studies on bilingual memory to studies on the role of the brain in language processing and language forgetting. This is a strong yet balanced combination of theoretical/overview contributions and accounts of novel, original, empirical studies which will educate readers on the relationship between theory, cognitive experimentation and data and their role in understanding language learning and practice"--